Ageing-induced hypercontractility is related to functional enhancement of STIM/Orai and upregulation of Orai 3 in rat and human penile tissue. (December 2021) - Sevilleja-Ortiz, Alejandro; El Assar, Mariam; García-Rojo, Esther; García-Gómez, Borja; Fernández, Argentina; Sánchez-Ferrer, Alberto; La Fuente, José M.; Romero-Otero, Javier; Rodríguez-Mañas, Leocadio; Angulo, Javier
Graphical abstract: Highlights: Role of STIM/Orai calcium entry system in vascular ageing is not elucidated. Ageing is related to Orai 3 upregulation in cavernosal tissues from rats and humans. STIM/Orai inhibition reverses hypercontractility of aged rat and human penile smooth muscle. Enhanced STIM/Orai signalling has a role in ageing-related vascular alterations. STIM/Orai inhibition could reduce impact of ageing on vascular and erectile function. Abstract: The role of STIM/Orai calcium entry system on vascular ageing has not been elucidated. We aimed to evaluate the influence of ageing on STIM/Orai signalling and its role on ageing-induced alterations of contractile function in rat corpus cavernosum (RCC) and human penile resistance arteries (HPRA) and corpus cavernosum (HCC). RCC was obtained from 3 months-old and 20 months-old animals. HPRA and HCC were obtained from organ donors of varied ages without history of erectile dysfunction. Aging was associated with enhanced norepinephrine (NE)- and thromboxane analogue (U46619)-induced contractions in RCC which were significantly inhibited by the STIM/Orai inhibitor, YM-58483 (20 μM). Other STIM/Orai inhibitor, 2-aminoethyldiphenylborate also reduced NE-induced contractions in RCC from aged rats. YM-58483 significantly reduced neurogenic contractions and potentiated neurogenic relaxations in RCC from aged rats. In HCC and HPRA, NE-induced contractions were significantly enhanced in older subjects (>65 years-old) but YM-58483 completely reversed ageing-related hypercontractility. Ageing did not modify STIM-1 and Orai1 protein expressions but Orai3 was significantly overexpressed in cavernosal tissue from old rats and older subjects. Contribution of STIM/Orai to cavernosal contraction increases with ageing together with increased expression of Orai3. Orai inhibition could be a potential therapeutic strategy to reduce ageing-related impact on vascular/erectile function.